2020
DOI: 10.1108/jkm-08-2019-0419
|View full text |Cite
|
Sign up to set email alerts
|

Organizational unlearning and knowledge transfer in cross-border M&As: the mediating role of knowledge integration from a routine-based view

Abstract: Purpose This paper aims to explore the relationships between organizational unlearning and knowledge transfer in cross-border mergers and acquisitions (M&As) from a routine-based view. The study also stresses the mediating role that knowledge integration capability plays in this relationship. Design/methodology/approach In all, 178 samples were collected from Chinese multinational corporations that experienced cross-border M&As. In addition, the bootstrap method was used to test the mediating role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 97 publications
0
37
0
Order By: Relevance
“…To mitigate these negative effects, some scholars highlighted the role of knowledge integration capability. For example, Xi et al (2020) argued that knowledge integration capability can not only facilitate knowledge transfer, but also help firms to design appropriate knowledge strategies. Moreover, Huang and Li (2017) found that knowledge integration capability can improve the efficiency of external knowledge acquisition and utilization.…”
Section: The Moderating Role Of Knowledge Integration Capabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…To mitigate these negative effects, some scholars highlighted the role of knowledge integration capability. For example, Xi et al (2020) argued that knowledge integration capability can not only facilitate knowledge transfer, but also help firms to design appropriate knowledge strategies. Moreover, Huang and Li (2017) found that knowledge integration capability can improve the efficiency of external knowledge acquisition and utilization.…”
Section: The Moderating Role Of Knowledge Integration Capabilitymentioning
confidence: 99%
“…However, given the knowledge distance between firms, it is not easy for firms to obtain and understand remote knowledge (Asimakopoulos et al, 2020). As Xi et al (2020) argued, knowledge integration capability is important for firms to update their knowledge routines. In turn, knowledge routines determine the extent to which firms search and absorb new knowledge (Koch, 2011).…”
Section: The Moderating Role Of Knowledge Integration Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-border M&As can provide opportunities and huge challenges for MNCs (Fuad and Gaur, 2019). Existing studies argued that MNCs frequently encountered various challenges such as post-merger integration (Bauer et al , 2018; Haapanen et al , 2019), human resource management (Liu and Meyer, 2020; Tarba et al , 2020), contextual differences (Ai and Tan, 2020; Li et al , 2016; Bauer et al , 2016) and organizational change (Xi et al , 2020). A considerable body of literature aimed to facilitate knowledge transfer by addressing these challenges.…”
Section: Theoretical Foundation and Frameworkmentioning
confidence: 99%
“…For example, Kamuriwo and Baden-Fuller (2016) explained how and why knowledge integration of nonmodular products based on a strategic choice between internalizing and outsourcing core R&D and found externally focused approach can avoid risks by framing non-modular outsourcing as modular; Caridi-Zahavi et al (2016) suggested that CEOs with visionary innovation leadership can help build knowledge integration capability and drive firm innovation; Oldroyd et al (2019) addressed that codified knowledge across borders can be a vital component for project‐based work while study the antecedents and performance effects of cross-border knowledge transfer. The researcher also mentioned some other ways, such as hiring external inventors, diversified innovators’ background (Rosenkopf and Almeida, 2003), through brokers or M&A (Hargadon and Sutton, 1997; Nooteboom et al , 2007; Xi et al , 2020), crowd-sourcing (Insead and Dahlander, 2015; Hargadon and Sutton, 1997), etc.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%